Ammonia volatilization and physiological growth of MR219 rice variety under split urea fertilization and chicken litter biochar amendment on tropical acid soil - Maikol, Nathaniel (2019)
Ammonia volatilization from nitrogenous fertilizers such as urea is high especially in paddy fields due to the anaerobic condition. This also leads to inefficient utilization of N in paddy fields thereby increasing the cost of rice production. Approximately, 40% of all soluble N applied to soils are lost via ammonification, denitrification, and leaching. The split application of N recommended by Muda Agriculture Development Authority (MADA), Malaysia indicates that N absorption in rice plants at different stages affects the concentration of NH4 + in the soil solution and this might also affect the amount of NH3 emitted in rice production. Clinoptilolite zeolite, coating urea, and soil organic amendments such as composts and biochars are used to minimize ammonia volatilization and in turn increases N used efficiency in rice production. Because of the surface charges (negative charges due to presence of -OH functional group) of chicken litter biochar, to improve soil CEC, texture, cations, anions and plants N uptake apart from minimizing ammonia loss from split application of urea. The specific objectives of this study were to determine the effects of split application of urea on: (i) on ammonia volatilization and selected physico-chemical properties of a tropical acid soil amended with chicken litter biochar for 111 days and (ii) on selected growth variables and N uptake up of MR219 cultivation on a tropical acid soil amended with chicken litter biochar. Treatments evaluated were: (i) T1, soil only, (ii) T2, existing recommended fertilization, (iii) T3, biochar alone, and (iv) T4, biochar + existing recommended fertilization in both pot and field trials. Ammonia volatilization were evaluated during incubation period in pot study and field trial for N uptake by plant was observes the changes in plants N uptake and soil N from the split urea application. Three replicates of each treatments in ammonia volatilization was arranged using Complete Randomized Design. In the field study, four replicates of each treatments arranged using Randomized Complete Block Design were evaluated in the field. Selected soil physicochemical properties and rice plant tissues were analyzed using standard procedures. The results on ammonia volatilization study revealed that the highest daily release of ammonia released was 8.22% and this emission is lower than the 11% to 10% and losses reported in the literature. Ammonia emission from the recommended fertilization was higher after third and fourth fertilizations. In this study, the chicken litter biochar reduces ammonia loss from day 70 to day 111 compared with that of the conventioal method. The acidity of the soils with chicken litter biochar were significantly lower than that of soil only. Considering the fertilization schedule of rice, ammonia emissions in rice production could be minimized if acidic soils under paddy cultivation are amended with chicken litter biochar. A further study into the N uptake and N use efficiency of the split fertilization showed that chicken litter biochar generally increased N uptake as compared with the conventional method. The N uptake increased after first, second, and third fertilizations after which the uptake significantly decreased because the rice plants were at panicle heading stages and most of the N was translocated for grain filling. Application of chicken litter biochar significantly increased Crop Recovery Efficiency and Agronomic Recovery Efficiency of applied N than in the conventional method. The Crop Recovery Efficiency started to decrease 40 days of transplanting of rice seedlings followed by rapid decrease in Crop Recovery Efficiency until 70 days after transplanting. The highest Agronomic Recovery Efficiency occurred on day 70 after which it significantly declined until 90 day. This was because of the translocation of most nutrients into rice grains production. The growth variables and yield of MR219 at harvest showed that plants height, number panicles, and grain yield of T4 were significantly higher than those of T1, T2, and T3 whereas those of T2 and T3 were similar but significantly higher than that of T1. Co-application of chicken litter biochar and chemical fertilizers increased rice grain yield of T4 to approximately 11.04 t ha-1 compared with the conventional method (T2) which yielded approximately 5.91 t ha-1. This indicates that the split fertilization of N should be increasing with increasing days of rice plants growth. The findings of this present study suggest that, applying 41.67% and 30.03% of N fertilization after 15 and 35 days of transplanting, respectively is not recommended especially for soils on which the conventional rice cultivation is practiced. Rather, the 41.67%, 30.03%, 14.15%, and 14.15% of total N recommended by MADA to be applied on the 15, 35, 55, and 75 days after transplanting could be modified to 26.67%, 30.03%, 30.15%, and 14.15% of total N on the 10, 30, 50, and 70 days after transplanting respectively, to further increase the rice plants N uptake, Crop Recovery Efficiency, Agronomic Recovery Efficiency, and rice grain yield.